Self-Government Bodies in Russia: Formation and Development Policies - Babaeva, Yulia; Lebedeva, Margarita; Mikhaylenko, Natalya; Olympiev, Anatoly; Soloviev, Andrey; Eriashvili, Nodari (Jurnal Cita Hukum, 2022)
The article aims at studying the legal nature and essence of local self-government bodies in the Russian Federation as exemplified by the theoretical and legal comprehension of the historical aspects of forming local self-government bodies. The article uses the methods of induction and systemic scientific analysis, as well as comparative-legal and historical methods. The authors of the article proved that the implementation of the principles of local self-government in the Russian state apparatus became effective since it is based on objective economic, political and social prerequisites and conditions. As a result, all cities and rural settlements became municipalities.Keywords: Local self-government; Constitution; Municipal authority; Municipal structure; Human rights. Badan Pemerintahan Lokal di Rusia: Kebijakan Pembentukan dan Pengembangan AbstrakArtikel ini bertujuan untuk mempelajari sifat hukum dan esensi dari badan-badan Pemerintahan Lokal di Federasi Rusia, sebagaimana yang dicontohkan oleh pemahaman teoretis dan hukum dari aspek-aspek sejarah pembentukan badan-badan pemerintahan lokal sendiri. Artikel ini menggunakan metode induksi dan analisis ilmiah sistemik, serta metode komparatif-hukum dan historis. Penulis artikel membuktikan bahwa penerapan prinsip-prinsip pemerintahan lokal sendiri di aparatur negara Rusia menjadi efektif karena didasarkan pada prasyarat dan kondisi ekonomi, politik dan sosial yang objektif. Akibatnya, semua kota dan pemukiman pedesaan menjadi kotamadya.Kata Kunci: Pemerintahan Daerah Lokal; Konstitusi; Otoritas Kota; Struktur Kota; Hak Asasi Manusia.Органы местного самоуправления в России: Политика формирования и развития АннотацияСтатья направлена на изучение правовой природы и сущности органов местного самоуправления в Российской Федерации на примере теоретико-правового осмысления исторических аспектов формирования органов местного самоуправления. В статье используются методы индукции и системного научного анализа, а также сравнительно-правовой и исторический методы. Автор статьи доказал, что реализация принципов местного самоуправления в российском государственном аппарате стала эффективной, поскольку основывается на объективных экономических, политических и социальных предпосылках и условиях. В результате все города и сельские поселения стали муниципалитетами.Ключевые слова: Местное самоуправление; Конституция; Муниципальная власть; Муниципальное устройство; Права человека.